Impacts of Temperature and Pressure on the Thermophysical Properties of Granites - Lixia Xu; Guiling Wang; Wei Zhang; Gaofan Yue; Yuzhong Liao (Energy Exploration & Exploitation, 2025)
The thermophysical properties of rocks are identified as basic physical parameters for the exploitation and utilization of hot dry rock (HDR) geothermal resources. Given that reservoirs in a HDR system are subjected to a certain temperature and pressure, investigating the impacts of temperature and pressure on the thermophysical properties of rocks holds great significance. This study investigated the granite samples from the Tengchong area, Yunnan Province, China. Using laboratory tests combined with simulations, this study explored the impacts of temperature, pressure, and the combination of both on the thermal conductivity and diffusivity of granites. The results indicate that in the uniaxial pressure range of 0 to 42.2 MPa, as the uniaxial pressure increases, the thermal conductivity of the granites tends to increase nonlinearly, while their thermal diffusivity has no obvious correlation with the pressure. In the temperature range of 25 to 300°C, as the temperature increases, both the thermal conductivity and diffusivity of the granites tend to linearly decrease, with a linear relationship existing between the thermal conductivity and diffusivity. Using these findings, this study developed a prediction model for the thermal conductivity of granites under the combined effects of temperature and pressure. Additionally, based on the computed tomography (CT) scans, this study established core-scale heat transfer models focusing on minerals using the COMSOL Multiphysics finite element analysis (FEA) software. The model has a certain reliability in the prediction of thermal conductivity at 25∼300°C, and the error is less than 15% at 25∼200°C.